A Rare Case of Giant Vein of Galen Malformation in an Adolescent Presenting with Hydrocephalus and Visual Impairment - Sharad Thanvi; Hitesh P. Bulchandani; Aman Raj; Lakhami Chand Sinsinwar; Rahul Rai (NMO Journal)
Vein of Galen aneurysmal malformations also known as vein of Galen malformations (VoGMs) are rare vascular malformations occurring commonly in the paediatric age group. They comprise only 1% of all intracranial vascular malformations, but in paediatric population, they represent 30% of all intracranial vascular malformations. They are of two types – mural and choroidal. The choroidal type of VoGM is more primitive and the most severe form of the disease. It usually causes high cardiac output failure in newborn period because of multiple high-flow fistulas. Adult presentation of choroidal type VoGM is very rare, and only a few cases have been reported in the literature so far. VoGMs result from persistent shunting of primitive choroidal vessels into the median prosencephalic vein of Markowski, and its presentation in an adolescent and adult is even rarer. VoGMs are associated with poor clinical outcomes with a reported 76.7% mortality if left untreated. We present an exceedingly rare case of a giant, untreated choroidal type of VoGM measuring 29 mm × 33 mm × 26 mm in a 16-year-old adolescent presenting with poor Glasgow Coma Scale, hydrocephalus and visual impairment. A total of 149 cases were identified from 1982 to 2020, and only 26 of them were described in adults and were published in English. The embryological origin, classification, clinical manifestations and different treatment options and treatment of choice of VoGMs are discussed in this report with a review of pertinent literature.